Sistem Kesehatan Tangguh Menghadapi Pandemi COVID-19: Kajian Ketahanan RSUD Haji Abdoel Madjid Batoe Batang Hari Jambi - J. EL- Matury, Herlina; Handayani, Shintya; Ginting, Selamat; Sari, Nur Mala; Sitorus, Friska Ernita; Sembiring, Bunga Mari; Batubara, Saiful (LPPM Hang Tuah Pekanbaru, 2023)
The COVID-19 outbreak is a global public health emergency of international concern. Cases of COVID-19 spread in many countries across the continent and were marked as a pandemic. COVID-19 is growing rapidly, requiring hospitals to prepare preparedness measures related to managing the pandemic while continuing to provide essential services to other patients who need treatment. This study aims to assess the resiliency capacity of RSUD Haji Abdoel Madjid Batoe Batang Hari Jambi against the COVID-19 pandemic. This research is a descriptive approach. Assessment using the N-COV Hospital Readiness Checklist. The results show that the readiness to respond to the COVID-19 pandemic shows an achievement of 95.6%, which means that HAMBA Hospital is ready to face the COVID-19 pandemic disaster. HAMBA Hospital has taken preparedness steps according to the guidelines from the World Health Organization (WHO) in handling.